Pengaruh Bimbingan Karir Terhadap Kemantapan Keputusan Karir Siswa Kelas XII SMK Swasta Bandung 1 - Lubis, Aismat Ihsan; Mahidin, Mahidin; Syukri, Makmur (STAI Denpasar Bali, 2024)
This research aims to find out: analyze whether there is an influence of career guidance on the career stability of Class XII students at Private Vocational School I Bandung. This type of research is quantitative quasi-experiment (quasi-experiment) with pre-test and post-test one group design. The subjects of this research were 32 students in class XII of Private Vocational School I Bandung. The sampling technique used purposive sampling. The data for this research was taken using a self-confidence questionnaire with 30 valid and realistic questions, then the data was analyzed using the SPSS test. Pre-test data to overcome feelings of lack of self-confidence obtained an average score of 2.045. Meanwhile, post test data on self-confidence obtained an average score of 3.875. This means that the average score of students after receiving group guidance services for career stability is higher than before receiving career guidance services for stability. From data analysis it is obtained that Fcount = 15 with a = 0.05 while Ftable = 4. From these data it can be seen that Fcount > Ftable where 15>4. This means that the hypothesis is accepted. The influence of career guidance on student career stability by contributing 33.4% to increasing the career stability of Class XII students at Private Vocational School I Bandung. This shows that there is an influence given or the hypothesis can be accepted.